Czy może istnieć świat rzeczy bez rzeczy? Problem badania inwentarzy dóbr w historii sztuki - Morawski, Konrad (Artium Quaestiones, 2019)
The paper addresses a problem which traditional art history has thus far ignored, i.e. the examination of items listed in inventories of property. Art historians usually approach concrete works of art to textualize them, while they are helpless confronting items “hidden” behind a text. In the context of the “materiality turn,” inventories reveal their paradoxical character since they include “personal” information about individual objects. If one assumes that the inventory is an instrument used to examine the objects listed in it, one must also realize a basic paradox of approaching them via their purely textual representation. A growing interest of art historians in publishing historical sources, in particular inventories, should result in more reflection on the role assigned to texts and things by historiography. To answer the question how items listed in inventories are available to their readers, the author has made references to cognitive linguistics and epistemology, critiques of historical narrativism, and poststructuralism. Such a comprehensive frame of reference made it possible to analyze some problems of the theory of historical source analysis and the editing and publishing of source texts. A comparison of art history and history of material culture resulted in defining the expectations and limitations related to the study of property inventories conducted by both disciplines. The experience of object analysis, which is a key prerequisite of interpretation, has been described in reference to three cognitive terms: concepts, exemplars, and invariants. The scholar trying to use all the available sources to reach the object itself must take advantage of all his/her experience. Analysis is possible only in a context, while the meaning of concepts, i.e. brief entries about individual items, can be discovered only in a complex system of semiotic reference. Apparently, such analysis can never be objective.